2020
DOI: 10.1007/s10461-020-02885-3
|View full text |Cite
|
Sign up to set email alerts
|

Using an HIV Self-test Kit to Test a Partner: Attitudes and Preferences Among High-Risk Populations

Abstract: For those most at risk of contracting HIV, new strategies for preventing transmission and increasing testing are needed. As part of a multi-site, randomized, controlled trial (RCT), we explored attitudes and preferences among 272 HIV-negative men who have sex with men and HIVnegative transgender women using an HIV self-testing (HIVST) kit to test partners. Less than one quarter had previously self-tested with HIVST kits (21.7%) and few had partner-tested (4.8%). Most preferred gum swab (96%) over fingerprick t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…With respect to the issue of cost and potential financial barriers, this project provided HIVST kits free of charge. Sale of HIVST kits is likely to have limited capacity to meet the need of those who want self-testing as, consistent with previous Australian [ 15 , 28 ] and international [ 41 ] research, many (50.8%) of the study participants indicated that they would not be willing to pay for an HIVST kit. In 2019, the TGA approved the Atomo Diagnostics™ rapid diagnostic finger-prick test in Australia for use as a self-test.…”
Section: Discussionsupporting
confidence: 54%
“…With respect to the issue of cost and potential financial barriers, this project provided HIVST kits free of charge. Sale of HIVST kits is likely to have limited capacity to meet the need of those who want self-testing as, consistent with previous Australian [ 15 , 28 ] and international [ 41 ] research, many (50.8%) of the study participants indicated that they would not be willing to pay for an HIVST kit. In 2019, the TGA approved the Atomo Diagnostics™ rapid diagnostic finger-prick test in Australia for use as a self-test.…”
Section: Discussionsupporting
confidence: 54%
“…Convenience was a key attribute for MSM who preferred home self-sampling [ 14 , 15 ] or self-testing [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Table 1 ). A study conducted in the UK used focus groups and interviews with 44 MSM to explore the acceptability of home self-sampling kits [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies identified that a feeling of obligation to protect themselves and their partners was an important reason for testing amongst MSM [ 14 , 15 , 19 , 22 , 39 , 40 ]. This finding was consistent across a variety of settings.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed a high level of acceptability of self-testing, as 93% reported it was likely they would use self-testing kits to test partners in the future. Only 5% of men reported problems with performing the test (17).…”
Section: Discussionmentioning
confidence: 96%
“…Badanie wykazało duży poziom akceptowalności testów do samodzielnego wykonania badania, gdyż 93% badanych zgłosiło prawdopodobieństwo wykonania szybkich testów do samodzielnego wykonania przez swoich partnerów w przyszłości. Jedynie 5% mężczyzn zgłosiło problemy z wykonaniem testu (17).…”
Section: Discussionunclassified